SISTEM PENDIDIKAN KARAKTER DI SMA ISLAM AS-SYAFI’IYAH PULO AIR SUKABUMI - Moh. Hifzul Muiz; Aan Hasanah (Cross-border, 2021)
Character education has become a hot discourse in the world of Indonesian education, including in institutions of Islamic education. Although the original idea of ​​character is an old idea as old as the history of education, the emergence of the idea of ​​"character building" interrupts our nation, especially those that are closely related to the problems being experienced. Problems that occur such as violence, corruption, manipulation, practices of lies in the world of education ranging from the simplest characters to the biggest ones. Actually everything is inseparable from the character problem. In addition, there are still many generations of our students who sit in school like in educational institutions, definitely really need character education so that in the future they become people who are not only intellectually intelligent but also have good character (good attitude). The world of education is expected to be a driving force in terms of the realization of good character. So in this case it is necessary to implement an appropriate character education system in the world of Islamic education in particular. Character education also has a noble goal, namely to build character and manners in life. Character restrictions fall into two areas. He is believed to exist as a natural human trait, while on the other hand he is believed to be "formed" through education, one of which is through character education in schools. Character education in schools such as the As-Syafi'iyah Islamic High School Pulo Air Sukabumi is also closely related to the management system or school management. Management in question is how character education is planned (planning), implemented (actuating), and controlled (evaluation) in educational activities in schools adequately. Such management includes values ​​that need to be instilled, curriculum content, learning, assessment, educators and education staff or other related components. Thus the purpose of character education will be realized properly if the character education system is good. Because the purpose of character education is to encourage the birth of good children, once they grow up in good character, children will grow up with the capacity and commitment to do the best things and do everything right, and tend to have an effective character education life goal found in a school environment that allows all students to show all their potential to achieve very important goals (Kepennas, 2010:11).